Comparison of Agility Between HPE and Non-HPE Girl Students of Secondary School - Shrestha, Mitra Lal (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
The main purpose of this research paper was to compare agility between HPE and Non-HPE students +2 level in Jana Prabhat secondary school, Kathmandu. The total of 40 students were taken for the study. The participants were 20 girl students of HPE and 20 girl students Non-HPE. These respondents were taken through purposive cum random sampling method. H. D. Edgren and AAHPER Youth Physical Fitness test was used by the researcher to find out the agility of HPE and Non- HPE students. The test battery included two test items namely shuttle run, Side-step and squat thrust. According to the significance comparison of the data with the help of z-test, the researcher found that no significance different in shuttle run, side step and squat thrust.